Immune‐mediated adverse reactions to vaccines - Stone, Cosby A. (Br J Clin Pharmacol, 2019)
Vaccination continues to be the single most important and successful public health intervention, due to its prevention of morbidity and mortality from prevalent infectious diseases. Severe immunologically mediated reactions are rare and less common with the vaccine than the true infection. However, these events can cause public fearfulness and loss of confidence in the safety of vaccination. In this paper, we perform a systematic literature search and narrative review of immune‐mediated vaccine adverse events and their known and proposed mechanisms, and outline directions for future research. Improving our knowledge base of severe immunologically mediated vaccine reactions and their management drives better vaccine safety and efficacy outcomes.